2007
DOI: 10.1167/iovs.06-0972
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decline in VIP-Positive Parasympathetic Nerve Fibers in the Human Submacular Choroid

Abstract: The results indicate a significant age-related decline in VIP-positive nerve fibers and vessel diameter in the submacular choroid in disease-free human donor eyes. These findings suggest that a decline in the neural control of ChBF and vessel diameter may explain the reductions in ChBF and its adaptive control observed clinically with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 53 publications
1
26
0
1
Order By: Relevance
“…In addition, we have shown that vasoactive intestinal polypeptide (VIP)-positive submacular choroidal nerve fi bers from human donor eyes decline with age (Jablonski et al 2007 ) and that, while donor eyes age 70-94 have, on average, 8.8% blood vessel VIP fi ber coverage, early AMD has 1.6% coverage, and advanced AMD has about 0.5% fi ber coverage (unpublished observation). VIP is both a potent vasodilator and a key local anti-infl ammatory and immunomodulatory agent (Gonzalez-Rey and Delgado 2005 ;Pozo et al 2007 ;Smalley et al 2009 ) .…”
Section: Preliminary Results From Our Research Support the Role Of Aumentioning
confidence: 96%
“…In addition, we have shown that vasoactive intestinal polypeptide (VIP)-positive submacular choroidal nerve fi bers from human donor eyes decline with age (Jablonski et al 2007 ) and that, while donor eyes age 70-94 have, on average, 8.8% blood vessel VIP fi ber coverage, early AMD has 1.6% coverage, and advanced AMD has about 0.5% fi ber coverage (unpublished observation). VIP is both a potent vasodilator and a key local anti-infl ammatory and immunomodulatory agent (Gonzalez-Rey and Delgado 2005 ;Pozo et al 2007 ;Smalley et al 2009 ) .…”
Section: Preliminary Results From Our Research Support the Role Of Aumentioning
confidence: 96%
“…These changes are also occurring in the context of reduced regulatory potential from the central nervous system–decreased parasympathetic innervation of the choroid has been described in aging in both pigeons (Fitzgerald et al, 2005) and man (Jablonski et al, 2007). Although we believe the most pronounced changes are occurring at the level of the microvasculature of the choroid, pathology of large vessels has also been suggested based on measurements of scleral rigidity, with increased resistance in the vortex veins, reflux and damage to the choriocapillaris and, ultimately, RPE atrophy (Friedman et al, 1989).…”
Section: Model For Amd Pathogenesismentioning
confidence: 99%
“…The innervation of the choroid includes roles for neurons that terminate on large vessel walls and that deliver the potent vasodilator nitric oxide (Li et al, 2010) as well as those without obvious innervation of vascular elements. The role of innervation in maintaining a healthy choroid is an important and active area of study (Fitzgerald et al, 2005; Jablonski et al, 2007; Li et al, 2010; Nickla and Wallman, 2010). …”
Section: Overview Of Choroidal Structure and Functionmentioning
confidence: 99%
“…Aging is also associated with a decrease in lean body mass and a relative increase in fat mass, and it has been suggested to result in a slow progressive redistribution of fat from subcutaneous tissue to central abdominal tissue (Borkan et al 1983;Barbieri et al 2001). Aging is also associated with a generalized reduction in parasympathetic nerve function demonstrated for the cardiovascular system (O'Brien et al 1986;Ingall et al 1990;Corbett et al 2007), eyes (Fitzgerald et al 2005;Tewari et al 2006;Jablonski et al 2007), GI tract (Phillips and Powley 2001, 2007, and urinary bladder (Schneider et al 2005). Parasympathetic dysfunction can be identified before development of diabetes (Lautt 1980), is later associated with the metabolic syndrome (Britton et al 2007) and obesity (Skrapari et al 2007;von Känel et al 2007), but improves with reduced adiposity (Mager et al 2006).…”
mentioning
confidence: 99%